2017
DOI: 10.1097/phh.0000000000000562
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Multipartner HPV Vaccination Assessment and Feedback Intervention in an Integrated Health System

Abstract: A collaborative approach was critical to engaging leadership and enlisting support from providers and to developing appropriate materials for clinical audiences. Information provided here can be used as a guide for conducting assessment and feedback interventions focused on HPV vaccination initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Baseline education sessions were presented to Family Medicine and Pediatrics departments in 9 KPNW clinics in April 2015; the content of the education sessions has been described elsewhere in detail. 11 Briefly, at each of these baseline education sessions a study team member paired with a health educator from the OIP to deliver the intervention. The study team member presented information on HPV disease and HPV vaccination using the Centers for Disease Control and Prevention-developed “You are the Key to Cancer Prevention” materials, as well as vaccine coverage and missed opportunity for HPV vaccine initiation at preventive care visit data tailored according to clinical department (Pediatrics and Family Medicine).…”
Section: Methodsmentioning
confidence: 99%
“…Baseline education sessions were presented to Family Medicine and Pediatrics departments in 9 KPNW clinics in April 2015; the content of the education sessions has been described elsewhere in detail. 11 Briefly, at each of these baseline education sessions a study team member paired with a health educator from the OIP to deliver the intervention. The study team member presented information on HPV disease and HPV vaccination using the Centers for Disease Control and Prevention-developed “You are the Key to Cancer Prevention” materials, as well as vaccine coverage and missed opportunity for HPV vaccine initiation at preventive care visit data tailored according to clinical department (Pediatrics and Family Medicine).…”
Section: Methodsmentioning
confidence: 99%
“…Similar education efforts have been previously published. 32,33 Patient navigators On-site PNs, funded through a prevention grant from the Cancer Prevention Research Institute of Texas (CPRIT), identified patients 9-17 years of age who were scheduled for wellchild visits, acute care, or specialty visits and were incompletely vaccinated or unvaccinated. At least one PN was assigned every day to each of the 3 clinics.…”
Section: Provider Educationmentioning
confidence: 99%
“…Educational interventions designed to target specific populations were effective in improving vaccine knowledge and this was usually associated with improved vaccine acceptance. Parents and caregivers were more confident in HPV vaccine when they were exposed to messages that addressed lack of knowledge about the vaccine [ 52 , 67 , 72 , 74 , 75 , 77 79 , 83 ]. Some of the educational interventions targeted providers, while others targeted young adults as catch-up populations.…”
Section: Introductionmentioning
confidence: 99%
“…Countries where HPV intervention studies were conductedMalpass et al, 2015),(Shah et al, 2019),(Baldwin et al, 2017),(Bonafide & Vanable, 2015),(Brewer et al, 2017),(Casillas et al, 2011),(Cates et al, 2018),(Chapman et al, 2010),(Cox et al, 2010),(Dempsey et al, 2006),(Diclemente et al, 2011),(Gerend & Barley, 2009),(Groom et al, 2017),(Hopfer, 2012), (Kennedy et al, 2011), (Lee et al, 2018), (McRee et al, 2018), (Obulaney et al, 2016), (Reiter et al, 2011), (Reiter et al, 2018), (Spleen et al, 2012), (Wetzel et al, 2007), (Zimmerman et al, 2017), (Bonville et al, 2019), (Dempsey et al, 2018), (Dempsey et al, 2019), (Dixon et al, 2019), (Gualano et al, 2019), (Hayes et al, 2019), (Kim & Hmielowski, 2017), (Krakow et al, 2017), (Kumar et al, 2019), (Roussos-Ross et al, 2017), (Suarez Mora et al, 2018), (Gilkey et al…”
mentioning
confidence: 99%